Creation and validation of an educational video for deaf people about cardiopulmonary resuscitation - Nelson Miguel Galindo-Neto; Ana Carla Silva Alexandre; Lívia Moreira Barros; Guilherme Guarino de Moura Sá; Khelyane Mesquita de Carvalho; Joselany Áfio Caetano (Universidade de São Paulo, 2019)
ABSTRACT Objective: to create and validate an educational video for teaching deaf students about cardiopulmonary resuscitation. Method: methodological study consisting in the creation of an educational video, validation of its content by 22 nurses with expertise in cardiorespiratory arrest, and evaluation by 16 deaf students. For data collection, the following validated instruments were used: the Instrument for Validation of Educational Content used for the validation by nurses and the Assistive Technology Assessment Questionnaire for the evaluation by deaf students. The criterion for validation was concordance higher than 80%, analyzed through the content validation index and binomial test. Results: the final version of the video lasted seven minutes and thirty seconds, covered the steps that should be performed by a lay person to help a victim of cardiorespiratory arrest, presented animations and the narration in the Brazilian sign language. All the items obtained agreement among nurses and of among deaf students equal or superior to 80%. Conclusion: the video was considered to present valid content by the judges and comprehensible content by deaf students. Thus the video represents an inclusive technology for health education of deaf people about cardiopulmonary resuscitation.